Structure and Expression Patterns of MADS box Transcription Factor, POTM1 in Potato (Solanum Tuberosum L.) - Kajal (TIET, Patiala, 2019)
POTM1 is a long distance travelling RNA transcript which acts as a mobile signal. It is highly expressed in both reproductive and vegetative organs in potato and other plants. The transcripts of POTM1 are accumulated in leaf primordial, apical and inflorescence meristem. POTM1 is a transcription factor (Mr~28.9 kDa) with pI value of 8.77. It is an important member of MADSbox superfamily which positively regulates the expression of potato genes such as StSP6A. As revealed in the literature, considerable progress has been made on the MADS-box transcription factors associated with various stages of growth and development in plants including the Solanaceae family members. This study focused on a particular member of the MADS-box family namely POTM1 since this gene function gained considerable importance with regard to a complex biological process like tuberization in potato. Several facile bioinformatics tools were employed in order to generate data in the following aspects: sequence identity, sequence analysis, multiple sequence alignment, searching protein motifs, and 3-D modeling along with some other attributes. Most of these features as obtained in this study were not reported earlier. Apart from in silico approaches, some experiments were carried out to know the expression patterns of POTM1 gene. For this purpose, total RNA was isolated from field-grown different potato organs namely leaf, flower, tuber, and tuberizing stolon. First, reverse transcription (RT) was carried out using organ-specific individual total RNA samples and POTM1 cDNA-specific oligonucleotide primer(s). Subsequently, the RT products were employed to carry out PCR. The size of the amplicon was ~1.0 kb. Similar amplicon was also found using potato genomic DNA as template. Possibly, there was no intron in the POTM1 gene. As evident from RT-PCR data, POTM1 transcripts were clearly detected in the tuberizing stolons and flowers. Probably this transcript level could be low or negligible in other potato organs. All these data are quiet useful and relevant with regard to the Indian potato cultivars particularly for the crop improvement aspects.
MSc Biotechnology thesis
Keywords: Potato (Solanum tuberosum L.) cultivars; POTM1 (potato MADS-box); Transcription factors; Self Pruning (SP6A); Reverse transcription (RT); Polymerase Chain Reaction (PCR)